Peru : Building a More Efficient and Equitable Fiscal Decentralization System - World Bank Group (World Bank, Washington, DC, 2019)
Over the past two decades, Peru has achieved remarkable economic success. Average annual Gross Domestic Product (GDP) growth has exceeded 5 percent since 2001. Poverty has been consistently reduced, and sustained improvements have been observed in social and human development. The poverty incidence rate fell from 58 to 23 percent between 2004 and 2014, and households’ incomes at the bottom 40 percent grew 50 percent faster than the national average. The structural transformation of Peru’s economy striking fast and widely shared growth transformed Peru into an upper-middle income and diversified economy. This report analyzes recent trends of the fiscal decentralization process in Peru and presents a set of reform options designed to harvest the envisaged efficiency and equity gains in service delivery that the fiscal decentralization was expected to bring. The analysis and policy options are presented in a conceptually logical order: (i) departing from institutional arrangements in the vertical structure of subnational governments passing to (ii) the need of a clearer definition of spending responsibilities among levels of government that needs to be followed by (iii) a commensurate redefinition of revenue assignments and (iv) enhancing equalization role of the transfer system.